IWR-1 Inhibits Collagen-Induced Platelet Activation and Protects against Thrombogenesis - Wang, Wei; Lai, Songqing; Xiao, ZiJin; Yan, Haiyue; Li, Yongxi; Zhang, Ye; Wu, Yanqing; Wang, Ling (Hämostaseologie, 2019)
Platelets play a crucial role in haemostasis and several pathophysiological processes. Collagen is a main initiator for platelet activation and aggregation. Given that Wnt signalling negatively regulates platelet function, and IWR-1 (a small molecule inhibitor for Wnt signalling) has the potential of inhibiting collagen synthesis, it is essential to investigate whether IWR-1 regulates collagen-induced platelet activation and protects against thrombogenesis. In the present study we found that IWR-1 pretreatment effectively suppressed collagen-induced platelet aggregation in a dose-dependent manner. In addition, IWR-1 also resulted in a decrease of P-selectin and phosphatidylserine surface exposure using fluorescence-activated cell sorting analysis. In vitro studies further revealed that IWR-1 had a negative effect on integrin a2β1 activation and platelet spreading. More importantly, the results from in vivo studies showed that IWR-1 exhibited a robust bleeding diathesis in the tail-bleeding assay and a prolonged occlusion time in the FeCl3-induced carotid injury model. Taken together, current results demonstrate that IWR-1 could effectively block collagen-induced platelet activity in vitro and in vivo, and suggest its candidacy as a new antiplatelet agent.
Keywords: IWR-1; collagen; platelet activation; thrombogenesis